Food composition of the diet in relation to changes in waist circumference adjusted for body mass index. - Dora Romaguera; Lars Ängquist; Huaidong Du; Marianne Uhre Jakobsen; Nita G Forouhi; Jytte Halkjær; Edith J M Feskens; Daphne L van der A; Giovanna Masala; Annika Steffen; Domenico Palli; Nicholas J Wareham; et al. (PLoS ONE)
Background Dietary factors such as low energy density and low glycemic index were associated with a lower gain in abdominal adiposity. A better understanding of which food groups/items contribute to these associations is necessary. Objective To ascertain the association of food groups/items consumption on prospective annual changes in "waist circumference for a given BMI" (WC(BMI)), a proxy for abdominal adiposity. Design We analyzed data from 48,631 men and women from 5 countries participating in the European Prospective Investigation into Cancer and Nutrition (EPIC) study. Anthropometric measurements were obtained at baseline and after a median follow-up time of 5.5 years. WC(BMI) was defined as the residuals of waist circumference regressed on BMI, and annual change in WC(BMI) (ΔWC(BMI), cm/y) was defined as the difference between residuals at follow-up and baseline, divided by follow-up time. The association between food groups/items and ΔWC(BMI) was modelled using centre-specific adjusted linear regression, and random-effects meta-analyses to obtain pooled estimates. Results Higher fruit and dairy products consumption was associated with a lower gain in WC(BMI) whereas the consumption of white bread, processed meat, margarine, and soft drinks was positively associated with ΔWC(BMI). When these six food groups/items were analyzed in combination using a summary score, those in the highest quartile of the score--indicating a more favourable dietary pattern--showed a ΔWC(BMI) of -0.11 (95% CI -0.09 to -0.14) cm/y compared to those in the lowest quartile. Conclusion A dietary pattern high in fruit and dairy and low in white bread, processed meat, margarine, and soft drinks may help to prevent abdominal fat accumulation.